2021
DOI: 10.3233/jad-201422
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Dementia Prevalence in the Wisconsin Longitudinal Study: Cohort Profile, Protocol, and Preliminary Findings

Abstract: Background: There is growing consensus that non-genetic determinants of dementia can be linked to various risk- and resiliency-enhancing factors accumulating throughout the lifespan, including socioeconomic conditions, early life experiences, educational attainment, lifestyle behaviors, and physical/mental health. Yet, the causal impact of these diverse factors on dementia risk remain poorly understood due to few longitudinal studies prospectively characterizing these influences across the lifespan. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Prior studies have shown that the TICS-M has a high sensitivity in the detection of dementia [ 29 , 36 ] but a low positive predictive value [ 34 ]. The TICS-M shows good test–retest reliability and high inter-rater reliability [ 37 ], as well as excellent sensitivity (99%) and specificity (86%), and is considered suitable for early screening of cognitive impairment [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown that the TICS-M has a high sensitivity in the detection of dementia [ 29 , 36 ] but a low positive predictive value [ 34 ]. The TICS-M shows good test–retest reliability and high inter-rater reliability [ 37 ], as well as excellent sensitivity (99%) and specificity (86%), and is considered suitable for early screening of cognitive impairment [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some of these cohorts have been continuously followed across the life course. One of the oldest is the Wisconsin Longitudinal Study (WLS), which has followed participants to an age where dementia can be ascertained [2]. WLS is based on a one-in-three random sample of Wisconsin high school graduates aged around 20 years, born between 1938 and 1940 (n = 10,317) and continually assessed, most recently in 2020 around age 83 years.…”
Section: Examples Of Birth Cohorts and Their Designsmentioning
confidence: 99%